(untitled) (Archives of Criminology, 1995)
1. The findings discussed in the paper have been obtained within an international research project aimed at comparing the extent of self-reported deviant behavior of youth 11 West-European countries (Finland, England, Nord Ireland the Netherland, Germany, Belgium, Switzerland, portugal, Greece, Spain and Italy), the United States and New Zealand. The questionnaire ultimately used in all countries participating in the project resulted from long negotiations and was in fact a compromise. It contained questions about both the respondents’ deviant behavior and their social situation with consideration to variables of importance from the viewpoint of the theory of social control. Deviant behavior was divided into the following six groups: l) behavior manifesting social maladjustment (as.e.g. truancy or stealing rides); 2) destruction of objects (vandalism); 3) appropriation of another person’s property; 4) aggressive behavior; 5) alcohol consumption; and 6) drug taking and selling. Examined were young people from Warsaw, born in the years 197l‒1978; the sample consisted of 701 persons aged 14‒21 at the time of the survey. At the moment of the interview, 80.5 % of respondents either had a job or went to school. Most respondents (65.9%) stated they were on good terms with their father. Even a greater proportion of 88.5% were on good terms with their mother. Ten percent of the sample had no contacts whatever with their father, and a much smaller proportion (2.3%) ‒ with their mother. Apart from 42 persons, respondents stated they had real friends; over a half had one to three such friends. The rest mentioned larger groups as their friends. Forty-seven percent had a girl- or boyfriend; two-thirds would like the relationship to last. Of the examined 363 boys, 84.8% had played truant from school at least once for one day. The proportion tended to grow bigger with respondents’ age. It showed a regular upward trend from 50% among the14-year-olds to 100% among boys of 23. Of the examined 383 girls, played truant, with the proportion reaching its peak value of l00% among the 2l-year-olds, and showing an upward trend from 33.3% among the 14-year-olds to 97.4% among girls of 19. Another widespread phenomenon was stealing rides on city buses, trolley buses, or trams. Those who had stolen a ride at least once constituted 95.9% of the boys and 89.3% of the girls. Stealing rides on trains or intercity buses was much less widespread. It was admitted by 35.8% of the boys and 22% of the girls. Driving a car or motorcycle without a license or a motorbike without a bicycle permit was admitted by 52.6% of the boys and 29.9% of the girls. A further act we inquired about was painting or spraying walls, buses, bus seats and stops, etc. Such acts were admitted by 22.9% of the boys and 12.7% of the girls. Still another group of acts qualified as vandalism includes acts that result in destruction of or damage to property. The largest group of both boyg and girls tend to vandalise school furniture (22.3% of the boys and 13% of the girls), as well as trees, bushes and flowers in parks and squares (18.2 and 10.1% respectively). Asked whether they had ever carried any weapon, such as a knife, club, knuckle-duster, or gas pistol, 43.3% of the boys and 26.6% of the girls answered in the affirmative. Relatively large were the proportions of boys (25.9%) and girls (10.7%) who had ever participated in brawls or group disturbances in a public place. A proportion of 7.2% of the boys and 1.8% of the girls admitted having beaten a stranger. Cases of beating a family member were occasional: they were admitted by 1.4% of the boys and 0.6% of the girls. Also a small proportion of 3.3% of the boys and 1.3% of the girls admitted having wounded another person with a knife, club or another weapon. Intentional arson was admitted by 5.5% of the boys and 1.2% of the girls. Offenses against property or acts consisting in appropriation of property without the knowledge or consent of its owner were related frequent in the sample. Of the 702 young persons, 55.1% had committed at least one of the listed fourteen categories of acts. This proportion is rather big the fact considered that average young people were examined. Of the 14 categories of acts against property consisting in its appropriation, the youth most often admitted shoplifting, purchasing stolen property, breaking and entering, and thefts at school. Questions relating to drugs concerned two points: the taking of drugs and their selling by respondents. The drugs inquired about were divided into two categories, each of them asked about separately: marihuana and hashish (the first category); and home-made poppy straw brew, heroin, cocaine and LSD (the second category). A proportion of 16.5% admitted having ever taken marihuana or hashish. Boys admitted this behawior more often than girls (with proportions of boys and girls balanced in the sample): every fifth boy and every eighth girl had experiences with this category of drugs. A much smaller proportion of 2% admitted having ever taken the second category of drugs. Answers stating that the respondent had ever taken marihuana or hashish were evenly distributed in the sample and tended to become more frequent with age. The declared use of the second category of drugs was very rare and evenly distributed in age groups from 16 to 21. Ten persons, among them 9 boys, admitted having sold marihuana or hashish. Most were aged 16‒18, that is still went to school. They stated that the police had never learned about their doings. Four persons admitted having sold the second category of drugs. They had sold amphetamine, cocaine, or psychedelic drugs in their neighborhood. None had been caught at the act. Asked, “Have you ever drunk beer, wine, vodka or another alcoholic beverage?”, nearly the entire sample (95.9% of the boys and 94.7% of the girls) answered in the affirmative. Asked about the age of their first contact with alcohol, 3.7% mentioned the age of under ten; 19.8% ‒10‒14; 48.3% ‒ 14‒16; and 17.l% ‒ 17‒21. The proportion of respondents who had happened to get drunk at least once was 56.3%. Asked about drinking during the year preceding the survey, 93.6% said they had drunk in that period; 50.3% admitted having drunk on up to 10 occasions, 18.1% ‒ on ll‒24 occasions, 10.6% ‒ on 25‒50 occasions, and 20.9% ‒ on over 50 occasions. The last time before the survey, the respondents drank: beer (43.8%), vodka (35.6%), wine (27.6%), and long drinks (10%). A majority of 86.5% drank in the company of others; under 10% had one companion, two-thirds of the rest drank in a group of 2‒10 persons, and the remaining ‒ in a larger company. In the international survey, national samples were examined in four countries (Switzerland, England and Wales, Portugal, and the Netherlands). In Spain, the survey concerned a large national urban sample. Examined in further two countries (Germany and North Ireland) were random samples from specific cities (Mannheim and Belfast respectively). Four other countries decided to examine a random sample of school youth from a specific city (Helsinki; three ltalian cities: Genova, Messina and Siena; Liege). The United States and New Zealand were left out from comparisons. Thus in principle the findings to be compared were not necessarily comparable. Yet it seems advisable to discuss the general trends shown in national surveys. What, therefore, are the similarities and dissimilarities between Poland and Western Europe? As regards the incidence of delinquency, considerable similarities can be noticed between findings of all national surveys but the English one. In surveys of city samples (those of school youth included), significant similarity can be noticed in the extent of delinquent acts “ever committed” by the young of Warsaw, Helsinki, and Athens. As regards the extent of acts committed “during last year”, the findings obtained in Warsaw are highly similar to those for Helsinki. In Athens, instead, the greatest extent of juvenile delinquency of all examined cities was found. A comparison of acts committed “during last year” indicates a similar intensity of offenses against property among the youth of Warsaw, Belfast, and Liege; as compared to Warsaw, a much greater extent of there offences is found in Helsinki and of Swiss youth, and a decidedly smaller one - in the English and Italian sample. Submitting offenses against property to a closer analysis, one notices that the Polish youth relatively more often commit acts consisting in “breaking and entering” as compared c.g. to young people in England, the Netherlands, or Finland: this type of act was committed at least once by 20.7% of the Polish sample, by 14.9% of the youth of Helsinki, by 3.4% of the English youth, and by 6.9% of the young Dutch. The extent of acts related to drugs (taking and trafficking), among Warsaw youth is similar to that among the young of Portugal and Helsinki, somewhat lower than among the Dutch and Spanish youth, much lower than among the English, Swiss, and Belfast young people, but higher than among the youth of Mannheim, Liege, Athens and the three Italian cities.